Prevalence and spatial distribution of cranberry fruit rot pathogens in British Columbia, Canada and potential fungicides for fruit rot management - Wood, Brandon; McBride, Ethan; Nabetani, Keiko; Griffin, Taylor; Sabaratnam, Siva (Frontiers in Plant Science, 2023)
Twenty eight cranberry farms in southwestern British Columbia were investigated for the prevalence and spatial distribution of fungal pathogens that contribute to fruit rot incidence. Farms were selected from six regions where most cranberry production is concentrated. Flowers, and green and ripe fruit (var. 'Stevens') samples, collected during two consecutive crop seasons, were analyzed for fruit rot pathogens. The most frequently isolated pathogens were identified as Allantophomopsis cytisporea, Botrytis cinerea, Coleophoma empetri, Colletotrichum fioriniae, Colletotrichum gloeosporioides, Fusicoccum putrefaciens, Glomerella sp., Phomopsis vaccinii, Phyllosticta elongata, Phyllosticta vaccinii and Physalospora vaccinii. The pathogens, Allantophomopsis cytisporea, Phyllosticta spp., and Physalospora vaccinii were found at high incidence. These pathogens were present in all cranberry growing regions, although their mean percentage incidence varied from farm-to-farm and region-to-region. Amongst the pathogens from three phenological stages of cranberry crop examined, ripe fruit had the highest percentage incidence of fruit rot pathogens compared to that of flowers or green fruit; thus, indicating their presence at the early stages of crop development. The efficacy to inhibit the mycelial growth and spore germination of the fruit rot pathogens by twenty six fungicides, belonging to nine different modes of actions, were evaluated in vitro. The copperbased fungicides and captan of group M, flutriafol, triforine, difenoconazole, prothioconazole and propiconazole of group 3, benzovindiflupyr of group 7, and fosetyl-Al of group 33 demonstrated a high degree of efficacy in inhibiting the mycelial growth of all fruit rot pathogens. The fungicides chlorothalonil of group M, fenbuconazole of group 3, pyrimethanil and cyprodinil of group 9, and fludioxonil of group 12 also demonstrated activity against most fruit rot pathogens. The copper-based fungicides, chlorothalonil, captan, flutriafol, triforine, difenoconazole, prothioconazole, propiconazole, benzovindiflupyr, and fosetyl-Al effectively prevented the spore germination of most fruit rot pathogens. This demonstrated activity of the fungicides towards cranberry fruit rot pathogens should be assessed for efficacy in planta under field conditions. The current study identified the most critical fungal pathogens causing fruit rot of cranberry in British Columbia and potential fungicides that could be used in the management of fruit rot and to improve fruit quality and yield.